The Hamas massacre of Oct 7, 2023, and its aftermath, medical crimes, and the Lancet commission report on medicine, Nazism, and the Holocaust - Shmuel P. Reis; Hedy S. Wald (BMC, 2024)
Abstract Background The report of the Lancet Commission on medicine, Nazism, and the Holocaust, released in November 2023, calls for this history to be required for all health professions education, to foster morally courageous health professionals who speak up when necessary. Main body The report was released a month after Hamas' October 7 invasion of Israel, with the accompanying massacre of over 1200 people, taking of civilian hostages, and gender-based violence. These acts constitute crimes against humanity including genocide. Post-October 7, war in Gaza resulted, with a legitimate objective of Israel defending itself within international law. The authors discuss an accompanying Statement to the report condemning Hamas crimes and denouncing the perpetrators' use of their own civilians as human shields, including in healthcare facilities, and with the Hamas attack unleashing immense and ongoing suffering in Israel and beyond. With some exceptions, the medical literature shows a marked absence of condemnation of Hamas atrocities and includes unsubstantiated criticisms of Israel's military. A significant surge in global antisemitism including on university campuses since October 7, 2023, has occurred; and health professionals, according to the Commission, have a special responsibility to fight antisemitism and discrimination of all kinds. In this context, the authors discuss the controversy and criticism regarding diversity, equity, and inclusion education programs ("DEI") including such programs failing to protect Jews on campuses, especially as the U.S. President Biden's "The U.S. National Strategy to Counter Antisemitism," released in May 2023, calls for the inclusion of issues of antisemitism and religious discrimination within all DEI education programs. The authors support an evidence-based approach to the Hamas massacre, its aftermath and its relevance to health professionals both within medicine and their global citizenship, including refuting the international community accusations and anti-Israel libel. Conclusions The report of the Lancet Commission on medicine, Nazism, and the Holocaust has striking relevance to the Hamas massacre of October 7, 2023 and its aftermath. This is further conveyed in an accompanying Statement, that describes the report's implications for contemporary medicine, including: 1) provision of skills required to detect and prevent crimes against humanity and genocide; (2) care for victims of atrocities; (3) upholding the healing ethos central to the practice of medicine; and (4) fostering history-informed morally courageous health professionals who speak up when necessary.